Association Between Beta-Carotene Supplementation and Mortality: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Corbi, Graziamaria; Ali, Sawan; Intrieri, Mariano; Modaferri, Sergio; Calabrese, Vittorio; Davinelli, Sergio; Scapagnini, Giovanni (Frontiers in Medicine, 2022)
Background. Aging is a phenomenon universally involving all organisms, genetically determined, and epigenetically influenced by the environment. Numerous observational studies have illustrated the positive impact of non-pharmacological approaches on chronic conditions affecting the elderly health and survival. This meta-analysis aimed to investigate the effect of beta-carotene on the total and cause-specific mortality as reported by randomized controlled trials (RCTs). Methods. We searched Medline, Scopus, Web of Science, and CENTRAL Cochrane from inception to September 2021. Studies were eligible if enrolled adults with any health condition, compared beta-carotene supplements at any dose with placebo or no intervention, provided information on deaths from any cause, and were randomized controlled trials, in English. The risk of bias was assessed by the Cochrane risk of bias tool and the GRADE. Risk ratios and their 95% confidence intervals were used and a P value less than 0.05 was considered statistically significant. Results. Among 3942 articles searched, 44 articles on 31 RCTs, which included 216734 total subjects, 108622 in beta-carotene supplement groups, and 108112 in the placebo or no-intervention groups, were involved in the final analyses. In a random-effects meta-analysis of all 31 trials, beta-carotene supplements were found to have no preventive effect on mortality (risk ratio 1.02, 95% confidence interval 0.98 to 1.05, I2=42%). Further, the analysis showed no preventive effect on cancer, cardiovascular, cerebrovascular, and other mortality causes. Instead, beta-carotene supplementation significantly increased the risk of lung cancer mortality (RR 1.14, 95% CI 1.02, 1.27, I2=3%) but decreased the risk of human immunodeficiency virus-related mortality (RR 0.55, 95% CI 0.33, 0.92, I2=0). Conclusions. More studies should be performed to better define the role of beta-carotene on survival, to confirm or deny our results. Therefore, the possible beneficial or harmful effects of the beta-carotene supplementation on mortality must not be overstated.